Potential Pathogens and Insects Responsible for Low Seed Production in Teak Seed Orchard and their Management - Dadwal, V. S.; Singh, Nisha; Meshram, P. B.; Prakasham, U. (Indian Forester, 2013)
Spermoplane micro flora of teak (Tectona grandis) seeds were recorded in the inflorescence, immature and mature stages of fruits. During the seed setting process Fusarium sp. shows systemic infection. Simultaneously some seed boring insects like Pagyda salvalis, Dichocrosis punctiferalis and D. pendamalis were also found associated with the teak fruits. Due to attack of these pathogens and insects, the fruiting in TSO’s and SPA’s are very less. One field experiment, using biopestcides (Bacillus thuringiensis, B.amyloliquefaciens), insecticides (Monocrotophos), fungicide (Bavistin), trace elements (Rallis tracel-2) and growth hormone (Planofix) in different combinations were applied in 16 years old TSO in Nandigram, Seoni, M.P.. The result of the experiment showed maximum number of fruits and weight of teak fruits in the treatment of Monocrotophos (0.05%) + Bavistin (0.2%), the insect and fungal damage was also less in the treatment. Whereas other treatment does not show significant result. Therefore, application of Monocrotophos nd st (0.05%) + Bavistin (0.2%) in the month of July and 2nd dose during 1st week of August can enhance fruit productivity in TSO’s.